The Effectiveness Of Tui Na Massage On Difficulties Of Eating In Children 1-3 Years Age In South Tangerang City In 2020 - Dessy R Susanti; Retno Widowati; Triana Indrayani (Health Media, 2020)
The growth and development of children is very dependent on the fulfillment of nutrition, problems in fulfilling nutrition such as difficulty eating in toddlers can cause growth and development disorders. One of the triggers for malnutrition is difficult eating behavior in children. Efforts to overcome eating difficulties can be done by pharmacological methods of giving mulvitamins and non-pharmacological methods of acupressure massage, herbs, acupuncture. The purpose of this study was to determine the effectiveness of tui na massage on feeding difficulties in children aged 1-3 years. This type of research is a Quasi Experiment with a one-group design with pre-test and post-test. The study population was toddlers aged 1-3 years. The sample in this study were 15 respondents aged 1-3 years old using purposive sampling technique. The results of the study used the Wilcoxon test data analysis. The results showed that Tui Na massage was effective in overcoming feeding difficulties in toddlers aged 1-3 years